PENGARUH KEFASIHAN MEMBACA AL-QUR’AN TERHADAP KETERAMPILAN MEMBACA PADA BIDANG STUDI BAHASA ARAB - Junaidi Junaidi; Baiq Mulianah (El-Tsaqafah : Jurnal Jurusan PBA, 2021)
This study aims to determine the effect of fluency in readingal-quran on reading skills in Arabic for Class X MA. Yusuf Abdussatar,Kediri Village, Kediri District, West Lombok. This approach is quantitativeresearch, because the data collected is in the form of numbers. In this study,there are several instruments that researchers use in collecting the requiredresearch data, including: (1) Observation guidelines / guides, this can be inthe form of columns containing the variables to be observed. (2) Interviewguidelines, namely. A collection of questions made as a guide in interviewingrespondents. (3) Questionnaire, namely, a data collection tool in the formof written questions addressed to respondents. (4) Documentation, namely,a data collection tool in the form of columns containing the situation andconditions of the research object. The data analysis used is the CausalComprativ study, which is used to explain the correlation or relationshipbetween two variables. The conclusion from the results of this study isthat there is an effect of reading fluency in the Qur’an on reading skills inthe field of study in Arabic for Class X MA. Yusuf Abdussatar Kediri, WestLombok, 2019-2020 Academic Year. This is evidenced by the number thatthe researcher got after conducting the research with the results obtained byrcount is (0.041) while the r table tested at a significant level of 5% with thetotal population (N) = 20 is 0, 012. This fact shows that rcount is greater thanr table (0.014> 0.012) thus the correlation value obtained from this study issignificant.